Aquaculture and fisheries biotechnology : genetic approaches - Dunham, Rex A. (CABI Pub., 2004)
The genetic improvement of fish for aquaculture and related fisheries is a field of research that has seen considerable advance. This book examines the area and should be of interest to advanced students and researchers in animal genetics, fish biology and aquaculture.